ANTARA ULAYAT ADAT DAN HUTAN NAGARI : SEBUAH KEBIJAKAN PERHUTANAN SOSIAL DI MINANGKABAU - Tresno Tresno; Rizka Fitri Ana; Muki Wicaksono; Auviar R Wicaksanti; Riche Deswita (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2018)
This article is the result from our fieldwork to observed about the rule of regulation the social forestry in South Solok, West Sumatera. As this research uses etnoscience approach where the informant will be choosed by perposive sampling. Since the rule of LHK/83 is implemeted in South Solok that became strategic place of political ecology for advantaging the village forest in the Customary Land of the Alam Surambi Sungai Pagu. Based on the results, there are differences in customary communal tenure between the darek region whose control is held by penghulu andiko, while the rantau region whose control is given to rajo. Rajo is the head of the tribe who is in 4 the customary land in Alam Surambi Sungai Pagu. In the Alam Surambi Sungai Pagu community, the forest processing is divided into three, namely; 1) ulayat suku is an unprocessed highland forest or rimbo gadang; 2) ulayat kaum or harato pusako tinggi, which is a land of ancestor from ninik nan salapan and ninik 60 kurang like rice fields or sawah and will be passed on daughters; 3) ulayat saparuik, also known as Harato Pusako Randah, is a family property from parents or property owned by their father and mother during marriage in the form of fields or rimbo randah. After the issuance of 5 decrees of The Village Forest in Alam Surambi Sungai Pagu, some of rimbo gadang began to be used as a Village Forest, moreover the use of the forest began to take into account the nagari government. Hence, the boundaries of 4 customary land begin to blur. In addition, the existence of Nagari Forest does not only provide the legality for the people of Alam Surambi Sungai Pagu, but also provides the benefits for outside communities, LPHN and mining companies.